Indonesia Stock Market Index (IDX) Before and During the Russian-Ukrainian War Period 2020-2023 - Iman Murtono Soenhadji; Venai Letisa Bidjae (Greenation Research & Yayasan Global Resarch National, 2024)
The objective of this study was to examine the impact of the Federal Reserve's interest rate, inflation, world oil price, and the exchange rate of the Indonesian Rupiah on the IDX Composite both before and during the Russia-Ukraine conflict. Data collected from the period January 2020 to June 2023.The study aimed to analyze the combined effect of these variables on the IDX Composite, as well as their individual effects. Additionally, the study sought to identify the variable that exerted the most significant influence on the IDX Composite during the period under investigation. This research employs quantitative data obtained from secondary sources. The data analysis techniques used in this study encompass classical assumption testing, multiple linear regression analysis, hypothesis testing, coefficient of determination analysis, and paired sample t-tests. The findings of this study elucidate that the Federal Reserve's interest rate, inflation, global oil prices, and exchange rates collectively influence the IDX Composite both before and during the Russia-Ukraine conflict. The pre-war global oil price and the Federal Reserve's interest rate during the conflict have a partial impact on the IDX Composite. World Oil Price before the war and the Fed Interest Rate during the war are the most dominant variables affecting the IDX Composite.